Pattern of Gastric Emptying after Vagotomy and Pyloroplasty. Issue 5864 (26th May 1973) - Colmer, M. R.; Owen, G. M.; Shields, R.
Abstract : The pattern and rate of gastric emptying have been studied in 16 patients before and after vagotomy and pyloroplasty. The rate of emptying, expressed as half life in minutes, was not greatly changed by operation. After operation, however, there was a rapid initial phase of emptying, particularly marked in patients who had post-vagotomy diarrhoea.